2012
DOI: 10.1007/s00415-012-6630-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyneuropathy in cerebrotendinous xanthomatosis and response to treatment with chenodeoxycholic acid

Abstract: Polyneuropathy has been reported in cerebrotendinous xanthomatosis (CTX), although its nature and possible association with certain genotypes and phenotypes are unclear. The effect of chronic administration of chenodeoxycholic acid (CDCA) on peripheral nerve conduction parameters is still debated. We report clinical, laboratory, and electrophysiological findings in 35 CTX patients. Twenty-six subjects (74.2 %) showed peripheral nerve abnormalities. Polyneuropathy was predominantly axonal (76.9 % of patients) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…It does, however, reduce abnormally elevated levels of cholestanol, apolipoprotein-B, apolipoprotein-A1, and albumin in the CSF and re-establishes the selective impermeability of the BBB . Improvements in neurophysiologic investigations: NCV and/or VEP (Ginanneschi et al 2013;Mondelli et al 1992;Mondelli et al 2001), EEG (Berginer et al 1984;van Heijst et al 1998), and bone mineral density (BMD) (Federico et al 1993;Martini et al 2013) have also been reported.…”
Section: Treatmentmentioning
confidence: 95%
See 1 more Smart Citation
“…It does, however, reduce abnormally elevated levels of cholestanol, apolipoprotein-B, apolipoprotein-A1, and albumin in the CSF and re-establishes the selective impermeability of the BBB . Improvements in neurophysiologic investigations: NCV and/or VEP (Ginanneschi et al 2013;Mondelli et al 1992;Mondelli et al 2001), EEG (Berginer et al 1984;van Heijst et al 1998), and bone mineral density (BMD) (Federico et al 1993;Martini et al 2013) have also been reported.…”
Section: Treatmentmentioning
confidence: 95%
“…Abnormalities in patients with CTX have been reported for visual evoked potential (VEP), somatosensory evoked potential (SSEP), brainstem auditory evoked potential (BAEP), and nerve conduction velocity (NCV) studies, which may reflect delayed central conduction (Pilo-de-la-Fuente et al 2011;Tokimura et al 1992;Ginanneschi et al 2013). Electromyography (EMG)/NCV findings demonstrating motor or sensorimotor axonal neuropathy, demyelinating neuropathy, and mixed neuropathy have been reported (Pilo-de-laFuente et al 2011;Ginanneschi et al 2013;Verrips et al 2000b). Electron-dense deposits and crystal formation are a consistent histologic feature in liver biopsies from CTX patients.…”
Section: Diagnosis and Testingmentioning
confidence: 99%
“…In the literature, the primary pathological type of polyneuropathy in CTX is still a matter of debate. Altered lipid metabolism may cause a problem in myelin synthesis and the loss of myelin-axon integrity, leading to axonal degeneration [5]. Based on the nerve conduction study in our patient, the pathology was considered to be the sensory-motor demyelinating type.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous reports have documented peripheral nervous system involvement in patients with CTX using a variety of measurement methods, including electrodiagnostic study, such as nerve conduction study and an electromyogram [3456], sural nerve biopsy [367], and muscle biopsy [6]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation